Avoiding Miscommunication in Acute Musculoskeletal Trauma Cases: Use of Standardized Reporting and Classification Schemes - Higgins, Luke J.; Alluwaimi, Fatma; Osgood, Greg; Wang, Ken; Carrino, John A. (Seminars in Musculoskeletal Radiology, 2013)
Classification schemes can be a key element of a structured radiology report, providing succinct guidance for clinical decision making. Classification systems delineate the location and morphological characteristics of fractures (diagnosis), may provide a graded measure of severity (prognosis), and ideally guide treatment options. Reports structured in this fashion optimize communication between the physician interpreting the examination and the physician directing the patient's treatment. This article reviews the concept and utility of standardized structured radiologic reporting based on templates or checklists to avoid miscommunication in the context of acute musculoskeletal trauma.
Keywords: musculoskeletal radiology; trauma; structured reporting; classification systems